Clinical Profile of Contact Dermatitis Patients at the Allergy-Immunology Division of Dermatology and Venereology Outpatient Clinic - Gabriel Rio Widipriyatama; Damayanti; Dewanti, Linda; Anggraeni, Sylvia (Faculty of Medicine, Universitas Airlangga, 2023)
Background: Contact dermatitis is an inflammatory skin response that can be caused by several things. This inflammatory reaction is most often caused by external compounds that become allergens or irritants to the body. Purpose: To evaluate the clinical profile of contact dermatitis patients at the allergy-immunology division of dermatology and venereology outpatient clinic of Dr. Soetomo general academic hospital. Methods: The sampling technique used in this study is a total sampling technique and was processed with Excel descriptively. Result: The most frequent age group diagnosed with contact dermatitis was the 20–45-year-old age group (45.5%). The most frequent gender was female (72.2%). The most frequent occupation was private employee (30.8%). The most frequent suspected causal factor was cosmetics (35.2%). Itching was the most common type of patient complaint (44.1%). Face was the most frequent location (30.8%). Erythematous macules were the most frequent clinical manifestation (45.9%). The diagnosis of contact dermatitis was divided into allergic contact dermatitis ACD (60.4%) and irritant contact dermatitis ICD (39.6%). The most frequent topical therapy was corticosteroid (53.2%). Meanwhile, the most systemic therapy is antihistamine (73.8%). Conclusion: ACD is more prevalent than ICD and is more prevalent in women between the ages of 20 and 45. The most prevalent occupation distribution is among private employees. Cosmetics are the most frequently suspected cause factor. Itch is the most common patient complaint. The face is where contact dermatitis occurs most frequently. Erythematous macules are the most frequent clinical symptom. Corticosteroids and antihistamines are the most commonly given medication.